2015
DOI: 10.1007/s00228-015-1860-9
|View full text |Cite
|
Sign up to set email alerts
|

The EU(7)-PIM list: a list of potentially inappropriate medications for older people consented by experts from seven European countries

Abstract: PurposeThe aim of the study was to develop a European list of potentially inappropriate medications (PIM) for older people, which can be used for the analysis and comparison of prescribing patterns across European countries and for clinical practice.MethodsA preliminary PIM list was developed, based on the German PRISCUS list of potentially inappropriate medications and other PIM lists from the USA, Canada and France. Thirty experts on geriatric prescribing from Estonia, Finland, France, the Netherlands, Spain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
419
2
21

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 367 publications
(445 citation statements)
references
References 40 publications
(86 reference statements)
3
419
2
21
Order By: Relevance
“…They were updated in 2015 to include drugs affecting or being affected by renal function, similar to this update of the AGS Beers Criteria . Similar tools have been developed in Europe . The current update of the AGS Beers Criteria confirms and extends this work with a rigorous independent evidence grading process, an open peer‐review comment period consistent with Institute of Medicine standards, and the addition of drug–drug interactions and renal dose adjustment.…”
Section: Discussionmentioning
confidence: 77%
“…They were updated in 2015 to include drugs affecting or being affected by renal function, similar to this update of the AGS Beers Criteria . Similar tools have been developed in Europe . The current update of the AGS Beers Criteria confirms and extends this work with a rigorous independent evidence grading process, an open peer‐review comment period consistent with Institute of Medicine standards, and the addition of drug–drug interactions and renal dose adjustment.…”
Section: Discussionmentioning
confidence: 77%
“…The tool analyses the patientʼs diagnoses, current medication, symptoms, biometric measurements (e.g., body mass index, blood pressure) and laboratory values, performs an electronic comprehensive medication review, and returns recommendations for drug discontinuation or modification based on the following components:

Indication and contraindication check for all prescribed drugs according to the diagnoses provided and the officially approved indications by the European Medicines Agency (EMA)

Forty rules and recommendations based on systematic reviews of clinical trial and observational study evidence on usage of the most commonly prescribed drugs in older patients [30]

Ninety-five rules and recommendations taken from the Evidence-Based Medicine electronic Decision Support (EBMeDS) database (http://www.ebmeds.org/web/guest/home). These recommendations in turn are derived from the NICE-approved Evidence Based Medicine Guidelines (EBMG; http://www.duodecim.fi/web/duodecimpublications/ebmg) to assure regular updating

RENBASE renal dosing decision support software (http://www.medbase.fi/en/professionals/renbase)Swedish, Finnish, INteraction X-referencing (SFINX) interaction check decision support software (www.medbase.fi/en/professionals/sfinx) [31]PHARAO decision support software on adverse drug reactions (http://www.medbase.fi/en/professionals/pharao)Check of drugs listed in the European list of potentially inappropriate medication for older patients [32]
…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a study conducted in New Zealand suggested that PIMs were utilized by 42.7% of the community-dwelling elderly patients 12. Thus, such practices may increase the risk of developing ADEs up to several folds 13. This problem has threatened the geriatric population all over the world.…”
Section: Introductionmentioning
confidence: 99%